Exploring the market for compressed natural gas light commercial vehicles in the United Kingdom - Jacqueline L. Kirk; Abigail Bristow; Alberto M. Zanni (2014)
This paper examines the potential market for natural gas as a transportation fuel in the light commercial vehicle sector in the United Kingdom. In order to understand this market and identify barriers to growth and possible solutions interviews were conducted with a number of professionals with experience in this market. These interviews were open and exploratory enabling the application of grounded theory techniques in analysis. Clear priorities for potential users were cost and carbon reduction and the main constraint a lack of refuelling infrastructure. Small scale and low cost policy interventions were identified, at national level including maintaining tax differentials; easing payload restrictions; and limited support for refuelling facilities alongside local policy initiatives, for example, restoring the exemption from the London Congestion Charge for gas vehicles, that could help to kick-start the market at least at a niche level. © 2014 The Authors.